Srbija na istorijskoj prekretnici 1944: slom monarhista i pobeda komunističkih snaga - Nemanja Dević (Dileme)
In mid-1944, Serbia was at a historic turning point. The Allies’ decision to support the communist side influenced the outcome of the years-long civil war and enabled the communists to take over the state. The previously dominant Chetnik movement suffered a number of major defeats at the hands of Partisan forces penetrating Serbia from Bosnia and Montenegro. Meanwhile, local Partisan forces strengthened; following the example of other parts of the country, guerrilla detachments evolved into divisions and corps of the Yugoslav National Liberation Army. Finally, in September 1944, the Red Army came to their aid, accelerating the liberation and making a key contribution to the expulsion of German occupying forces. Based on existing literature and archival sources, the paper aims to provide an overview of thesituation in Serbia in the summer and autumn of 1944 and to highlight key factors leading to the Partisan takeover.